Selective Laser Melting: Materials and Applications - Konda Gokuldoss, Prashanth (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Additive manufacturing (AM) is one of the manufacturing processes that warrants the attention of industrialists, researchers, and scientists. AM has the ability to fabricate materials to produce parts with complex shapes without any theoretical restrictions combined with added functionalities. Selective laser melting (SLM), also known as laser-based powder bed processing (LPBF), is one of the main AM process that can be used to fabricate wide variety of materials that are Al-, Ti-, Fe-, Ni-, Co-, W-, Ag-, and Au-based, etc. However, several challenges need to be addressed systematically, such as development of new materials that suit the SLM process conditions so the process capabilities can be fully used to produce new properties in these materials. Other issues in the field are the lack of microstructure-property correlations, premature failure, etc. Accordingly, this Special Issue (book) focuses mainly on the microstructure-correlation in three different alloys: AlSi10Mg, Ti6Al4V, and 304L stainless steel, where six articles are presented. Hence, this Special Issue outlines microstructure-property correlations in the SLM processed materials and provides a value addition to the field of AM.